Electrocautery effect on intestinal vascularisation in a murine model. (17th August 2016) - Tremblay, Jean-François; Sideris, Lucas; Leblond, François A.; Trépanier, Jean-Sébastien; Badrudin, David; Drolet, Pierre; Mitchell, Andrew; Dubé, Pierre
Abstract: Background: The use of electrocautery devices is associated with complications such as perforation or fistulisation when used near intestinal structures. This is likely due to its effect on vascularisation of the bowel wall. To test this hypothesis we established a murine model to quantify the effect of electrocautery injury on the intestinal microvascularisation. Methods: Sprague-Dawley rats were subjected to five electrocautery injuries on the small bowel in coagulation mode (30 W intensity) and in cut mode (40 W, 80 W and 200 W intensities) for durations of 1, 2 and 5 s. 5 mg/kg of fluorescein was injected intravenously, the injured bowel segments harvested and the rat sacrificed. The segments were analysed to measure the fluorescence of injured bowel compared to adjacent unharmed tissue. Results: A significant decrease in bowel wall microvascularisation occurred with increasing intensity (coag 30 W/cut 40 W versus cut 200 W 1 s: p < 0.05) and duration of electrocautery injury (cut 40 W 1/2 s versus 5 s: p < 0.05). There was a 40% perforation rate when decreased bowel wall microvascularisation was 25% or more. Despite similar electrocautery injury, a significantly greater microvascularisation decrease was observed in jejunum compared to ileum ( p < 0.05). Conclusion: We successfully established a murine model to quantify the decrease of bowel wall microvascularisation associated with electrocautery use. Unsurprisingly, the decrease in microvascularisation is greater with higher intensity and duration of electrocautery and is associated with more perforations in the experimental model. The jejunum seems more vulnerable to electrocautery injury than the ileum. These observations support caution when using electrocautery devices near intestinal structures.